Social presence of an affiliate marketer in an online product photo, consumer’s clickthroughs and sales - Michalik, Martyna (Społeczna obecność marketera afiliacyjnego w komunikacji wizualnej produktu, konwersja online i sprzedaż, 2019)
The goal of this article is to answer the question: what actions in the area of communicating online social presence increase the consumer’s clickthroughs and online sales of the promoted offer in the affiliate marketing context. Six cases that concern visual communication of social presence, consumer’s clickthroughs and sales have been analysed in the study. A replicable relationship between visually communicating social presence on a Facebook fan page and on the affiliate’s blog, consumers’ clickthroughs and sales value have been identified. Managerial implications of the research results are that affiliates should communicate: 1) product in use, 2) photo made by the affiliate, and expect a positive impact on both clickthroughs in the tracking link and sales. New knowledge from this study is the identified impact of social presence in visual communication on sales, while the authors of earlier studies checked the impact of social presence only on trust, purchase intent or likes, comments and conversion online
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 184-195
Keywords: affiliate marketing; social presence; blog; fan page; visual communication; case study research; marketing afiliacyjny; obecność społeczna; komunikacja wizualna; badania przypadków